2011
DOI: 10.3791/2074
|View full text |Cite
|
Sign up to set email alerts
|

Pseudofracture: An Acute Peripheral Tissue Trauma Model

Abstract: Following trauma there is an early hyper-reactive inflammatory response that can lead to multiple organ dysfunction and high mortality in trauma patients; this response is often accompanied by a delayed immunosuppression that adds the clinical complications of infection and can also increase mortality. [1][2][3][4][5][6][7][8][9] Many studies have begun to assess these changes in the reactivity of the immune system following trauma. [10][11][12][13][14][15] Immunologic studies are greatly supported through the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 40 publications
1
45
0
Order By: Relevance
“…23,24 We demonstrate that LPS acting through TLR4 promotes Mϕ necroptosis, as expected. However, release of HMGB1 from damaged tissue signals via RAGE signaling to upregulate caveolin-1 expression and so induces Mϕ surface TLR4 internalization, which results in amelioration of LPS-TLR4-induced Mϕ necroptosis.…”
Section: Figure 1 Continuedsupporting
confidence: 82%
See 4 more Smart Citations
“…23,24 We demonstrate that LPS acting through TLR4 promotes Mϕ necroptosis, as expected. However, release of HMGB1 from damaged tissue signals via RAGE signaling to upregulate caveolin-1 expression and so induces Mϕ surface TLR4 internalization, which results in amelioration of LPS-TLR4-induced Mϕ necroptosis.…”
Section: Figure 1 Continuedsupporting
confidence: 82%
“…The PF model consists of two parts: a musclecrush injury to the hind limbs, followed by injection of a bone solution into these injured muscles. 24 In the current study, we used the PF model to elucidate the influence of tissue damage on LPS-induced Mϕ necroptosis, and revealed that HMGB1 within the BCM acts through RAGE signaling and is a major component mediating tissue damage-suppressed Mϕ necroptosis in response to LPS. Necroptosis is a regulated form of inflammatory cell death.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations